KEMAMPUAN DALAM MENULIS SCRIPT PADA MAHASISWA KEDELAPAN KELAS MTS Nahdlatul ULUM KECAMATAN TAPUNG KABUPATEN KAMPAR - Elfi Ulfa Masfufah; H. M. Nur Mustafa; H. Nursal Hakim (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research aims to find out the students’ ability in writing script at the eighth grade students of MTs Nahdlatul Ulum Kecamatan Tapun Kabupaten Kampar. This research uses descriptive method which is used to explain about the data that has been got. This research also uses writing script test technique. The descriptions of this reseach are: (1) prologue compatibility, (2) dialogue compatibility, (3) epilogue compatibility. The purpose of this research is to describe the students’ ability in writing script at eighth grade students of MTs Nahdlatul Ulum Kecamatan Tapung Kabuapten Kampar related to prologue, dialogue, and epilogue aspects. The participants of this research consist of 28 students for the population and 28 students for the sample. The result of this research shows that (1) the students’ ability in writing prologue is good, (2) the students’ ability in writing dialogue is average, (3) the students’ ability in writing epilogue is low.Keywords: writing, script, prologue, dialogue, epilogue.